2013
DOI: 10.1097/pec.0b013e31828e572d
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Emergency Department Observation Unit for Children With Abdominal Pain

Abstract: The majority of children admitted to the EDOU with abdominal pain have nonsurgical causes of abdominal pain. The EDOU provides a reasonable alternative for monitoring these patients pending disposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Many institutions have developed outpatient observation units, with 36% of US EDs reporting having observation units in 2007. Multiple studies have demonstrated that use of observation for a limited time in dedicated units can provide equivalent quality care at lower cost than inpatient care for select conditions including toxicology, skin infections, chest pain, syncope, atrial fibrillation, heart failure, and abdominal pain . Unfortunately we were not able to evaluate observation units separated from observations performed in other areas of the hospital and not dependent from the ED.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many institutions have developed outpatient observation units, with 36% of US EDs reporting having observation units in 2007. Multiple studies have demonstrated that use of observation for a limited time in dedicated units can provide equivalent quality care at lower cost than inpatient care for select conditions including toxicology, skin infections, chest pain, syncope, atrial fibrillation, heart failure, and abdominal pain . Unfortunately we were not able to evaluate observation units separated from observations performed in other areas of the hospital and not dependent from the ED.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple studies have demonstrated that use of observation for a limited time in dedicated units can provide equivalent quality care at lower cost than inpatient care for select conditions 2 including toxicology, 38 skin infections, 39 chest pain, 40 syncope, 41 atrial fibrillation, 2,42 heart failure, 43 and abdominal pain. 44 Unfortunately we were not able to evaluate observation units separated from observations performed in other areas of the hospital and not dependent from the ED. The strengths of our study are the use of "real-world" data outside clinical trials that allow us to compare rates of procedures related to patients with chest pain, large sample size, inclusion of multiple academic and nonacademic institutions across the United States, rigorous methodology during the selection of the patients and matching analysis, and measuring healthcare utilization within the ED and in the following 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…5-7 This may result in a diagnostic and therapeutic approach toward suspected constipation that varies from than algorithms used in the standard outpatient setting. Children undergoing disimpaction in the acute setting are more likely to experience pain relief in comparison to less aggressive therapies, and thus disimpaction per rectum is often employed.…”
Section: Introductionmentioning
confidence: 99%
“…Appendicitis is the most common acute surgical condition of the abdomen in children. It is diagnosed in up to 10% of children presenting with acute abdominal pain at the emergency department . Appendicitis is rare in pre‐school children, representing around 10% of all paediatric cases .…”
mentioning
confidence: 99%
“…It is diagnosed in up to 10% of children presenting with acute abdominal pain at the emergency department. 1 Appendicitis is rare in pre-school children, representing around 10% of all paediatric cases. 2 Despite all diagnostic advances, such as inflammatory markers, radiological tests and clinical prediction rules and protocols, misdiagnosis rates at initial evaluation in pre-school children can reach up to 50%, 3 mainly due to the variable and non-specific presentation and overlap of symptoms with many other common childhood illnesses, together with the difficult abdominal exploration and inability of the child to communicate.…”
mentioning
confidence: 99%